Pious vanity: Two pairs of 18th century abbesses’ knitted gloves - Odstrčilová, Sylvie (Archaeological Textiles Review, 2020)
Two pairs of silk knitted gloves from the graves of abbesses of St George’s convent in Prague Castle, Czech Republic, were compared. Both pairs are decorated with similar knitted-in patterns in metallic yarn, but they differ significantly in the knittng methods used and the skills of their creators. The gloves of Abbess Isidora Konstancie Roudnická (died 1731) were shaped by irregular increases and decreases using various methods and uneven yarn tension which resulted in a variety of loop sizes. In contrast, the gloves of Abbess Aloisie Theresie von Widmann (died 1735) were shaped only with right decreases and left raised increases placed in neat lines producing knitted fabric which is dense and even. The most interesting features of the gloves are the slits in the thumbs and the first two fingers of Abbess Isidora’s gloves.